Increased serum interleukin-17A levels correlate with disease severity and poor prognostic factors in patients with alopecia areata - Trang Le Thi Thuy; Thang Nguyen Tat; Chuyen Thi Hong Nguyen; Hao Nguyen Trong; Trung Van The (PAGEPress Publications, 2021)
Background: Alopecia areata (AA) is a tissue-specific autoimmune disease characterized by non-scarring and rapid onset of hair loss. Interleukin (IL)-17A is mainly produced by T helper 17 (Th17) cells and may play a crucial role in the pathogenesis of various autoimmune diseases including AA. Objectives: We conducted this research to measure serum level of IL-17A in patients with AA and investigated its relationship with the clinical manifestations in patients with AA. Methods: We assessed 36 patients with AA and 20 healthy control subjects. Demographic information and clinical characteristics were determined by physical examination and via the review of medical history. Serum IL-17A was measured by using enzyme-linked immunosorbent assay. Results: Serum IL-17A concentration was significantly higher in patients with AA than in the control group (P=0.004). The AA patients with severe presentation, personal atopy, nail abnormalities, or active phase had significantly higher serum IL-17A levels compared to others without these signs. Conclusion: Increased serum IL-17A levels in patients with AA correlate with severity and indicate an active disease state. These findings suggest that IL-17A may play an important role in determining the pathogenesis of AA and may serve as a valuable clinical biomarker of this disease.